Potential of open-air hydroponic system in producing highly nutritional composition maize fodder for goat farming - Whay, Chuin Lim; Mohd Nadzir, Mohd Noor Hisham; Hiew, Mark Wen Han; Mamat @ Mat Nazir, Md. Shuhazlly; Nazli, Muhamad Hazim; Shohaimi, Shamarina (Universiti Putra Malaysia Press, 2022)
This study aimed to identify the chemical composition of hydroponic maize fodder (HMF) from two varieties of maize grains (popcorn and feed corn). A completely randomized design (CRD) with three replications was used in which popcorn was irrigated with clean tap water (T1) and nutrient solution (T2); feed corn irrigated with clean tap water (T3) and nutrient solution (T4). Seven-days green fodders were sampled for chemical analysis. The crude protein (CP) content was the highest at 7.48% in T4 compared to popcorn (P<0.05) and T3 (P>0.05). Treatment 3 showed the highest dry matter content as 94.42% (P>0.05) and organic matter content observed as 98.29% especially compared with T1 (P<0.05). The neutral detergent fiber (NDF) and acid detergent fiber (ADF) contents of feed corn were insignificantly different, but T3 was observed as 67.66% and 41.55%, respectively, which were higher than T1 (P<0.05). Although feed corn had better nutritional value than popcorn, popcorn showed a 7% higher germination rate than feed corn (P<0.05). As a result, the total yield of 1.5 kg hydroponic maize fodder per kg feed corn was lower than popcorn (2.5 kg per kg grains). Hence, popcorn was used to grow HMF with the open-air hydroponic system. HMF showed better feed nutritive composition than conventionally planted Napier grass. A lower concentration of indigestible fiber (P<0.05) and a higher concentration of crude protein (12.28%) was observed in HMF compared to CP in Napier grass (7.22%) (P<0.05). In conclusion, the open-air hydroponics system can be an alternative method among smallholders by replacing conventionally planted fodder.